Characteristics of Tropical Cyclones Making Landfall on the Pacific Coast of Mexico: 1970-2014 - Farfán Molina, Luis Manuel (2015)
Póster -- Universidad de Costa Rica. Centro de Investigaciones Geofísicas. Actualización del trabajo: Farfán, L., E. Alfaro and T. Cavazos, 2013: Characteristics of tropical cyclones making landfall on the Pacific coast of Mexico: 1970-2010. Atmósfera, 26(2), 163-182. Como parte de la participación en el taller virtual: Observing & Modeling Climate Variability in the Intra-Americas Seas & Impacts on the Continental Americas and Caribbean (https://usclivar.org/meetings/2015-iasclip-virtual-workshop). https://usclivar.org/meetings/2015-iasclip-virtual-workshop-poster-gallery. Sep., 9-11, 2015.